An experiential approach to learning about change management. Issue 9 (6th November 2019) - Vandangeon-Derumez, Isabelle; Djedidi, Amina; Szendy, Eila
Abstract : Purpose: The purpose of this paper is to focus on the role of experience in learning about, and preparing for, change management. Design/methodology/approach: A course with a different approach to teaching about change management has been proposed to learners. It uses drawing, simulation and exploration of case studies. Learners wrote reports on change management before and after the course and these reports were then thematically analyzed. Findings: Results show the specific ways in which the course places learners in a position to: experience change, use their collective experiences, acquire and develop practical knowledge, and prepare themselves for change. Capitalizing on such experiences of change could arguably become an integral part of an organization's "readiness to change" strategy. Research limitations/implications: It would be useful to further investigate what happens after this experience by interviewing learners, later on, in order to analyze how they subsequently use, in a real professional environment, such knowledge and skills acquired during the learning process. Practical implications: Using this approach, future managers are arguably better prepared to implement change. Capitalizing on such experiences of change could become part of an organization's "readiness for change" strategy. Social implications: The benefits of experiencing change management in a learning environment will only be reaped when firms allocate time and space to such experiential learning. This entails going beyond managing this change to a deeper perspective by identifying key elements to maintain and/or enhance one's experience of managing change. Originality/value: The value of the present paper lies in individual and collective experience as a key element to prepare managers to change management.